(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
Education is the foundation of a nation’s progress since it shapes its economy and society. Sufficient financing in education is inevitable for overall development of national economy because all sectors’ skilled and expert manpower are produced from educational institutions. Proper financing makes the educational institutions and their programs more efficient to provide quality education. This study aims to explore the sources of educational financing in Nepal and examine the distribution of educational financing across different levels and types of institutions. This study employed desk review approach to bring rigorous and useful information of study issues. Desk review research method was taken as an appropriate because it allows for the synthesis of existing evidences, policy documents, and research findings. This study found that the main sources of educational financing are government, external donors, private institutions, and community contributions. Findings show that the significant portion of educational funding goes to school level, while higher education receives a smaller portion. Government funding in education in Nepal remains about 11% of total national budget and 3-4% of GDP but government itself committed to spend 20% of total budget to fulfil SDG goal 4 and (United Nations Educational Scientific and Cultural organization (UNESCO) recommended 4-6% of GDP. These budget inequalities have a significant impact on learning outcomes and educational equity because insufficient financing can restrict student support services, infrastructure development, and instructional quality. This study recommends to increase in government funding in education, strong oversight, equitable private sector regulation, and more stable funding for critical program to achieve constitutional and SDG goals.